MENGOPTIMALKAN SUMBER DAYA ARKEOLOGI SEBAGAI DAYA TARIK WISATA UNTUK KETAHANAN BUDAYA (Studi Kasus Sumber Daya Arkeologi di Provinsi Papua) [Optimizing Tourisme Attractions for Cultural Endurance: A Case Study of Archaeological Resources in Papua] - Ni Komang Ayu Astiti (BALAI ARKEOLOGI PAPUA, 2016)
Development of the tourism sector contributes a sizeable foreign exchange after oil and gas, coal, and oil palm. The government has also set a target of 20 million foreign tourists visit and 275 local tourist movement In 2019. Entering the era of globalization the movement of people from one country and region more quickly because the distance is getting closer, so it supports the growth of tourism . These conditions have a positive impact on the economy and science and technology, but social change is very vulnerable to the Impact on the weakening of the resilience of culture in society. For that how to increase the resilience of culture by minimizing the negative effects of tourism development in the era of globalization in Papua is very important. Trend rating is currently more concerned about the quality of experience and a tendency to look for something unique and authentic and can not be found in the region or country. To meet market demand trends and this can be done by presenting archaeological resources in Papua as a tourist attraction. Optimizing the archaeological resources in Papua as a tourist attraction that can be empowered to improve the resilience of culture in addition to providing economic benefits is the goal of this research. The study was conducted with the literature study and survey and using descriptive analysis techniques - qualitative. From the results of analysis show that Papua has the potential archaeological resources can still be presented authenticity and contextualization. Unlock the value of cultural and archaeological resources significance in the present context to make it as a tourist attraction in Papua embryonic formation of a positive image and local identity as multi cultur values, solidarity, unity and unity, mutual assistance and proud of their own culture. AbstrakPembangunan sektor pariwisata membarikan kontribusi devisa yang cukup besar setelah minyak dan gas, batubara, dan keispa sawit. Pemerintah juga teiah menetapkan targat kunjungan 20 juta wisman dan 275 pergerakan wisatawan nusantara di tahun 2019. Memasuki era globallsal pergsrakan manusia dari suatu Negara dan daerah semakin cepat karena jarak semakin dekat, sehingga sangat mandukung pertumbuhan pariwisata. Kondisi ini mempunyai dampak positif di bidang ekonomi dan IPTEK, tetapi perubahan sosial sangat rentan yang berdampak pada melemahnya ketahanan budaya di masyarakaL Untuk itu bagaimana meningkatkan ketahanan budaya dengan meminimalisasi pengaruh negatif pembangunan pariwisata pada era globalisasi di Papua sangat periling dilakukan.Trend wisatawan saat ini lebih memperhatikan kualitas pengalaman dan kecenderungan untuk mencari sesuatu yang unik dan otentik serta tidak ditamukan di daerah atau negaranya.Untuk memenuhi trend dan permintaan pasar ini dapat dilakukan dengan menyajikan sumber daya arkeologi di Papua sabagai daya tank wisata. Mangoptimalkan sumber daya arkeologi di Papua sebagai daya tarik wisata agar dapat diberdayakan untuk meningkatkan ketahanan budaya masyarakat seiain msmberikan manfaat ekonomi merupakan tujuan dari panelitian ini. Penelitian dilakukan dengan studi pustaka dan survei serta menggunakan teknik anallsls deskriptif-kualitatif. Dari hasil analisis diketahui bahwa Papua mempunyai potansi sumber daya arkeologi masih Mengoptimalkan sumber daya arkeologi sebagai daya tarik wisata untuk ketahanan budaya